Dinâmica espacial de Iracema: uma pequena cidade do Estado de Roraima - Olivares, Carlos Teodoro Olivares (2021)
The occupation process in the Amazon caused many socio-spatial and environmental changes. It is necessary to understand the main motivations that originated this process, as well as its historical evolution and the main agents in this spatial dynamic of the city of Iracema, identified as a small Amazonian city in the state of Roraima. Territorial policies in the Amazon region from the 1950s to the 1970s were important incentives for the occupation and colonization process, with a focus on the development of agricultural and livestock production centers, to supply the capitals. In this context, the research sought to expand knowledge about a city in Roraima with emphasis on the urban area; the interdisciplinary nature of the research brought discussions about occupation and spatial dynamics in the Amazon and, also establishing a dialogue between Geography and Architecture. In the first stage of the research, a study was carried out with the theoretical foundation, definition of some concepts such as space, spatial dynamics, architectural typologies, land uses and urban equipment. In a second stage, the historical chronology in which the spatial dynamics of Iracema is inserted was described and analyzes of the application of public policies that reflect on the spatial dynamics of Iracema were presented. In the third stage, concepts of a small sustainable city in the Amazon were presented: Sustainable Amazon Plan and the 2030 agenda. Finally, the conclusions of the research and discussions are intended to be a guiding document for further research on the topic of spatial dynamics in an urban area. Small town in the Amazon.